Radiation inactivation analysis of amino acid transport systems in Neurospora crassa - B. G. DeBusk; J. Mallon; A. G. DeBusk (Fungal Genetics Reports, 1965)
Radiation inactivation analysis of amino acid transport systems in Neurospora crassa